Peri-implant bone response to retrieved human zirconia oral implants after a 4-year loading period: a histologic and histomorphometric evaluation of 22 cases - Kohal, Ralf-Joachim; Schwindling, Franz Sebastian; Bächle, Maria; Spies, Benedikt Christopher (Journal of biomedical materials research. Part B, Applied biomaterials, 2016)
Aim To evaluate the bone tissue response to surface modified zirconia oral implants retrieved from humans. Materials and Methods Twenty-nine one-piece zirconia implants showed increased marginal bone loss and did not response to the applied peri-implantitis therapy. After their removal using a trephine bur, 22 of the implant-bone biopsies were suitable for an evaluation and immediately immersed in formalin for two weeks. Subsequent, the retrieved specimens were histologically prepared and the regions still showing osseointegration computer-assisted analyzed regarding the bone-to-implant contact (BIC) and bone density using a transmitted-light microscope. Results The removed implants were in situ for a mean time period of 47.7 months. After their removal, compact bone could be depicted at the apical regions. The remaining bone that was attached to the implants contained a regular lamellar structure with osteons and osteocytes. The BIC ranged from 58.1% to 93.7% (mean: 76.5%) and the bone area/density within the implant threads ranged from 57% to 97.2% (mean: 84.8%). Conclusions The porous zirconia implants showed a sufficient BIC in the areas where bone still was attached. Although the implants had to be removed due to increased bone loss, it seems that the presented zirconia implant surface per se elicited appropriate osseointegration. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1622-1631, 2016.
Gesehen am 06.05.2020
First published: 31 August 2015